Stabilization/solidification of lead contaminated soil using cement incorporated with sugarcane bagasse - Mohammad Azmi, Mohamad Azim (2015)
Soil that is contaminated with heavy metals, especially lead (Pb) has become a major issue worldwide. Pb is reported to be a metal that affects human health and is related to have caused serious diseases that interrupts the nervous system, blood vessels and kidneys. However, proper treatment techniques such as Stabilization/Solidification (S/S) method can be employed and is capable of controlling these heavy metals from contaminating the soil strata and groundwater resources. This research is to investigate the effect of soil strength and leachability of lead in S/S method when sugarcane bagasse (SCB) is added to remedy contaminated soil. Synthetic contaminated soil was prepared in bulk by mixing soil samples with lead nitrate, Pb (NO3)2 to achieve the concentration of 500 ppm. After that, cement is added at a proportion of 5%, 10% and 15% in sample weights without SCB while in another sample, the cement replaces SCB at a proportion of 2.5%, 5% and 7.5%. All samples were allowed to harden and cured at room temperature for 7, 14 and 28 days. The effectiveness of the treatment was assessed by conducting physical testing such as Unconfined Compression test, Density test and Water Absorption test. In addition, leaching tests were performed to identify the leachate criteria of lead during treatment. Two leaching tests were conducted and they were the Toxicity Characteristic Leaching Procedure (TCLP) and Synthetic Precipitation Leaching Procedure (SPLP). Results indicate that pH and leachability are found to have major influence on metal release. The final pH after leaching tests showed improvements especially samples containing SCB. In addition, the concentration of lead in the TCLP and SPLP test after the curing period of 28 days were detected to be below the leachability limit as regulated by the United States Environmental Protection Agency (US EPA). As a whole, the results obtained from testing showed that soil samples : 7.5% cement : 7.5% SCB is the most effective and is the optimum mix since this proportion succeeded in minimising the leachability of Pb as low as 2.11 mg/L or a total reduction by 99%, and it even produced the strength of 1389 kPa within 28 days. In conclusion, partial replacement of cement with SCB in the binder system has been successful in increasing the strength and reducing the leachability compared to the controlled sample.